2017
DOI: 10.1111/gbi.12241
|View full text |Cite
|
Sign up to set email alerts
|

Microbial acceleration of aerobic pyrite oxidation at circumneutral pH

Abstract: Pyrite (FeS ) is the most abundant sulfide mineral on Earth and represents a significant reservoir of reduced iron and sulfur both today and in the geologic past. In modern environments, oxidative transformations of pyrite and other metal sulfides play a key role in terrestrial element partitioning with broad impacts to contaminant mobility and the formation of acid mine drainage systems. Although the role of aerobic micro-organisms in pyrite oxidation under acidic-pH conditions is well known, to date there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 90 publications
(120 reference statements)
8
57
3
Order By: Relevance
“…Apart from iron-oxidizers isolated earlier from inactive sulfides in the East Pacific (Eberhard et al, 1995;Edwards et al, 2003), a Thiomicrospira strain capable of autotrophic growth with pyrrhotite as electron donor was recently isolated from surface sediment near Santa Catalina Island . Biotic acceleration of pyrite oxidation at neutral pH by freshwater Alpha-and Betaproteobacteria was also recently shown in borehole sediment (Washington, USA) enrichment cultures (Percak-Dennett et al, 2017). Notably, the genomes obtained from these enrichments by Percak-Dennett et al (2017) encoded the same metabolic potential in terms of cytochromes, sulfur oxidation and carbon fixation pathways as the gammaproteobacterial bins obtained in this study.…”
Section: Sulfide-oxidizing Woeseiaceae and Other Gammaproteobacteriasupporting
confidence: 78%
See 2 more Smart Citations
“…Apart from iron-oxidizers isolated earlier from inactive sulfides in the East Pacific (Eberhard et al, 1995;Edwards et al, 2003), a Thiomicrospira strain capable of autotrophic growth with pyrrhotite as electron donor was recently isolated from surface sediment near Santa Catalina Island . Biotic acceleration of pyrite oxidation at neutral pH by freshwater Alpha-and Betaproteobacteria was also recently shown in borehole sediment (Washington, USA) enrichment cultures (Percak-Dennett et al, 2017). Notably, the genomes obtained from these enrichments by Percak-Dennett et al (2017) encoded the same metabolic potential in terms of cytochromes, sulfur oxidation and carbon fixation pathways as the gammaproteobacterial bins obtained in this study.…”
Section: Sulfide-oxidizing Woeseiaceae and Other Gammaproteobacteriasupporting
confidence: 78%
“…Biotic acceleration of pyrite oxidation at neutral pH by freshwater Alpha-and Betaproteobacteria was also recently shown in borehole sediment (Washington, USA) enrichment cultures (Percak-Dennett et al, 2017). Notably, the genomes obtained from these enrichments by Percak-Dennett et al (2017) encoded the same metabolic potential in terms of cytochromes, sulfur oxidation and carbon fixation pathways as the gammaproteobacterial bins obtained in this study. Supporting the hypothesis of active interaction with the mineral surface, we found a gammaproteobacterial multi-heme cytochrome c to be the third most abundant annotated protein in the StM-R1 metaproteome.…”
Section: Sulfide-oxidizing Woeseiaceae and Other Gammaproteobacteriasupporting
confidence: 78%
See 1 more Smart Citation
“…According to Rojaschapana et al, the oxidizability of Leptospirillum ferrooxidans went beyond that of Fe 3+ alone. To further understand the oxidation mechanism of pyrite in the presence of microorganisms, Percak‐Dennett et al conducted their experiment in circumneutral pH. They found that the thin (30–50 nm) coatings of amorphous Fe(III) oxide were formed during the pyrite oxidation process, with no other secondary Fe or S phases detected.…”
Section: Pyrite Oxidationmentioning
confidence: 99%
“…Biegler and Swift [86] found that SO 4 2− and S 0 were formed in the anodization process in H 2 SO 4 solution. At the TABLE 1 Pyrite oxidation mechanism proposed by Percak-Dennett et al [68] Reaction Mechanism [31] pyrite went through the following steps during the electrochemical oxidation process. The first step is: FeS 2 !…”
Section: Electrochemical Oxidation Of Pyritementioning
confidence: 99%